Linkages Between the Real Sector and the Financial Sector: The Case of Malaysia - Siti Muliana Samsi; Zarinah Yusof; Kee-Cheok Cheong (Asian Academy of Management Journal of Accounting and Finance, 2012)
This paper aims to explore the dynamic interaction between the real sector and the financial sector in Malaysia during the period 1986:1 to 2011:4, a period in which the global crisis have been felt. The parsimonious error-correction model (PECM) is used to examine the significant role of financial variables on real output in the long-run as well as in the short-run. The findings suggest the existence of a long-term relationship between the real output and the financial sector. The causality tests reveal that the real output has strong relationships with the real estate and banking sector. From the PECM, the contribution of the banking sector is higher than that from other financial indices. The Kuala Lumpur stock exchange and the real estate contribute the same percentage to the output growth. Meanwhile, financial services accounted a small percentage to the output growth. This finding concludes that the better development in the banking sector stimulates GDP growth in Malaysia. Therefore, for sustainability of output growth, strengthening and establishing a well-developed banking sector is essential.